2018
DOI: 10.1038/s41467-018-04732-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation as a mediator of HLA-DRB1*15:01 and a protective variant in multiple sclerosis

Abstract: The human leukocyte antigen (HLA) haplotype DRB1*15:01 is the major risk factor for multiple sclerosis (MS). Here, we find that DRB1*15:01 is hypomethylated and predominantly expressed in monocytes among carriers of DRB1*15:01. A differentially methylated region (DMR) encompassing HLA-DRB1 exon 2 is particularly affected and displays methylation-sensitive regulatory properties in vitro. Causal inference and Mendelian randomization provide evidence that HLA variants mediate risk for MS via changes in the HLA-DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
145
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 77 publications
9
145
2
2
Order By: Relevance
“…Overall, the PBMC-based methylomes of the 45 MS discordant MZ twins were highly similar, as the mean within-pair β -value differences were very small (<0.05). None of the MS-DMPs observed in our study have previously been reported by other EWAS for MS [19][20][21][22][23][24][25] .…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Overall, the PBMC-based methylomes of the 45 MS discordant MZ twins were highly similar, as the mean within-pair β -value differences were very small (<0.05). None of the MS-DMPs observed in our study have previously been reported by other EWAS for MS [19][20][21][22][23][24][25] .…”
Section: Discussioncontrasting
confidence: 69%
“…Since these other studies used genetically unmatched cases and controls [19][20][21][22][23][24][25] , the large methylation differences observed by them might mainly be driven by genetic variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several HLA Class II and I alleles contribute to MS susceptibility, the main one is carriage of the HLA DRB15:01 haplotype (odds ratio (OR) of ~3). This gene variant is carried by 25–30% of the population in northern Europe and the USA.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…Autoproliferation of Th1 lymphocytes appears to be elevated in HLA‐DR15 ‐positive individuals and mediated by memory B cells in a HLA‐DR‐dependent manner . Interestingly, the DRB15:01 gene is epigenetically regulated, leading to increased expression and antigen presentation …”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%